PENGAJARAN BAHASA JEPANG TINGKAT DASAR BAGI ANAK ANAK SEKOLAH DASAR BALI BESTARI DI KELAS V - Betty Debora Aritonang; Khazya Nanda Suryo Atmojo; Putu Ayuk Septiani; I Gede Arya Weda; I Ketut Adi Putra Bonitu (Fakultas Bahasa Asing, 2024)
We could see Bali as an international tourist destination got the impact of globalization from more and more number of foreigners stay, live and work in Bali every year. One of the many foreign residents living in Bali is Japanese, so the needs to master Japanese will benefit Japanese language learners, especially if they are taught from an early age. The teaching team held this program as community service activities at Bali Bestari elementary schhool in Denpasar. The purpose of this activity is as a means of introducing basic level Japanese language and culture to fifth grade students at Bali Bestari Elementary School. The selection of lesson materials is adjusted based on the length of period, students grade and school needs. The lesson materials are vocabulary or sentences that are often used in the daily lives of elementary school students and the school environment. This teaching activity implemented into 4 stages, namely: 1. Observation and interviews, 2. preparation stage, 3. Implementation stage and 4. Monitoring and discussion stage. The results of the activity shows that students are able to say several daily greetings and vocabulary in dailyenvironments and students are able to implement Japanese culture which is demonstrated through attitudes when giving daily greetings and also in daily class activities.